TREATMENT OF INDUSTRIAL WASTE WATER USING REVERSE OSMOSIS TECHNIQUE (Journal of Engineering, 2009)
Reverse osmosis technique was used for the treatment of industrial waste water. Ions like calcium, magnesium, sodium, sulfate, and nitrate were found in the waste water of the General Company of Vegetable Oil with high concentrations which must be treated for reuse. Feed water containing the above mentioned ions was fed to the RO unit at feed flow rates (0.4 and 0.8 lit/min) and different operating pressure (2-4bar) .It is concluded that increasing operating pressure and feed flow rate improved the separation by a decrease in the concentration of ions in the product. High rejection was obtained for all ions present in feed water, ranging from (63.8-97.6%). Rejection of TDS was 87% when the concentration of TDS was reduced from 1192 to 154.94 ppm.